2014
DOI: 10.2134/agronj2013.0108
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emissions with Enhanced Efficiency Nitrogen Fertilizers in a Rainfed System

Abstract: The use of enhanced efficiency N fertilizers can increase crop N utilization and lead to lower emissions of the greenhouse gas N 2 O. To determine the potential benefit of four enhanced efficiency fertilizers with rainfed corn (Zea mays L.) production in central Pennsylvania, N 2 O emissions and grain yield were monitored during a 4-yr field study and compared with untreated urea prills and urea-NH 4 NO 3 (UAN). The tested enhanced efficiency products were ESN (polymer-coated urea), SuperU (urease and nitrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 19 publications
2
23
2
Order By: Relevance
“…Few other patterns were observed except that the control tended to have the lowest N 2 O flux throughout most of the study, which is logical given that no N was applied. While some researchers have reported reductions in daily N 2 O flux with use of nitrification inhibitors (Mosier et al, 1998; Jumadi et al, 2008) or EENFs (Halvorson et al, 2010a,b; Halvorson et al, 2011; Halvorson and Del Grosso, 2012; Asgedom et al, 2014), others have reported few differences between commercial fertilizers and EENFs (Parkin and Hatfield, 2014; Dell et al, 2014) as seen in the current study. Sistani et al (2011) found that ESN had lower daily N 2 O emissions early in the growing season but higher emissions after a 3 to 4 wk delay compared with other fertilizers.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…Few other patterns were observed except that the control tended to have the lowest N 2 O flux throughout most of the study, which is logical given that no N was applied. While some researchers have reported reductions in daily N 2 O flux with use of nitrification inhibitors (Mosier et al, 1998; Jumadi et al, 2008) or EENFs (Halvorson et al, 2010a,b; Halvorson et al, 2011; Halvorson and Del Grosso, 2012; Asgedom et al, 2014), others have reported few differences between commercial fertilizers and EENFs (Parkin and Hatfield, 2014; Dell et al, 2014) as seen in the current study. Sistani et al (2011) found that ESN had lower daily N 2 O emissions early in the growing season but higher emissions after a 3 to 4 wk delay compared with other fertilizers.…”
Section: Resultscontrasting
confidence: 45%
“…Soil N 2 O production primarily occurs through nitrification and denitrification processes (Firestone and Davidson, 1989). Nitrification has been identified as the primary source of N 2 O in many aerobic soils, and denitrification being the primary source under anaerobic conditions (Bremner, 1997; Dell et al, 2014). Denitrification has been reported to occur in anaerobic microsites within partially aerated soils, which also contributes to the N 2 O loss budget (Parkin, 1987).…”
mentioning
confidence: 99%
“…Vented chambers were constructed following a design presented in Dell et al (2014). Stainless steel cafeteria serving pans (Vollrath Corporation, Sheboygan, WI) were used with a port fitted on top for sampling with a needle and syringe.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 99%
“…Most research suggests greater N 2 O emissions will occur with a higher N rate (Lessard et al, 1996;Jarecki et al, 2009;Dell et al, 2014;Halvorson et al, 2014). For example, Lessard et al (1996) reported a 0.47 kg ha -1 increase in N 2 O emissions when dairy manure rates increased from 170 to 339 kg N ha -1 .…”
mentioning
confidence: 99%
“…In cotton production in the southeast, there was no effect of EEF materials on yield or fiber quality (Watts et al, 2014). The majority of the studies evaluated the effect of EEF materials on corn yield and showed inconsistent effects on grain yield (Dell et al, 2014;Halvorson and Bartolo, 2014). The use of EEF materials caused an increased greenness in corn canopies in Iowa and increased grain yield because of the delayed senescence of the plant canopy .…”
mentioning
confidence: 99%